PELATIHAN LESSON STUDY UNTUK MENINGKATKAN KOMPETENSI PROFESIONALISME GURU SEKOLAH MENENGAH PERTAMA - Subhanadri Subhanadri; Muhammad Hakiki; Arisman Sabir; Sari Guswita (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2021)
The purpose of this community service activity is to improve the professionalism of teachers or educators at SMP Negeri 7 Muara Bungo through lesson study training. The methods used are lectures and discussions. This training was attended by 29 teachers from various other fields of study at the school.Lesson study training consists of three stages, namely Plan, Do, and See. The informant plan the lessons to be implemented, such as preparing learning tools and media that will be used for lesson study activities. Then, the teacher carries out the plan stage, while other teachers act as observers. The implementation stage is called (the Do stage). The see stage, the teacher with the observer or observer, reflects on the implementation of the activities in the class. This activity adds to teachers' knowledge about lesson study and gets new experiences for teachers so that they can increase teacher professional competence.